PENGEMBANGAN WISATA HALAL PADA KAWASAN WISATA MANDEH KECAMATAN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - juli hendrita; Sri Mariya (JURUSAN GEOGRAFI FIS UNP, 2019)
The purpose of this study to developed the Mandeh tourism area into a halal tourism attraction in terms of aspects such as tourism forms, characteristics and criteria for halal tourism, and halal tourism management. The type of this research is qualitative descriptive with the location of the research in Mandeh tourism area of Koto XI Tarusan Subdistrict, Pesisir Selatan District. The results showed that the Mandeh tourism area is a family friendly which is the area suitable for all ages in terms of tourism numbers form of individuals, families and groups tourism. Based on the characteristics of halal tourism, food and beverages contained in mandeh tourism areas are in accordance with the characteristics of halal tourism because the traders do not use food ingredients that are prohibited by Islamic religion. The worship facilities for Muslims (musholla and mosques) in the tourist area of Mandeh are in accordance with the criteria of halal tourism which are seen based on the complete facilities of worship and purification. In terms of management, the Department of Tourism, Youth and Sports of the Pesisir Selatan Regency has a role as coordinator whos making policies, facilitators are facilitating tourism objects, and stimulating tourism development, namely attracting investors to invest in Mandeh tourist areas, while the community acts as a formator and tourism manager.